Targeting von Willebrand Factor in Ischaemic Stroke: Focus on Clinical Evidence - Buchtele, Nina; Schwameis, Michael; Gilbert, James C.; Schörgenhofer, Christian; Jilma, Bernd (Thrombosis and Haemostasis, 2018)
Despite great efforts in stroke research, disability and recurrence rates in ischaemic stroke remain unacceptably high. To address this issue, one potential target for novel therapeutics is the glycoprotein von Willebrand factor (vWF), which increases in thrombogenicity especially under high shear rates as it bridges between vascular sub-endothelial collagen and platelets. The rationale for vWF as a potential target in stroke comes from four bodies of evidence. (1) Animal models which recapitulate the pathogenesis of stroke and validate the concept of targeting vWF for stroke prevention and the use of the vWF cleavage enzyme ADAMTS13 in acute stroke treatment. (2) Extensive epidemiologic data establishing the prognostic role of vWF in the clinical setting showing that high vWF levels are associated with an increased risk of first stroke, stroke recurrence or stroke-associated mortality. As such, vWF levels may be a suitable marker for further risk stratification to potentially fine-tune current risk prediction models which are mainly based on clinical and imaging data. (3) Genetic studies showing an association between vWF levels and stroke risk on genomic levels. Finally, (4) studies of patients with primary disorders of excess or deficiency of function in the vWF axis (e.g. thrombotic thrombocytopenic purpura and von Willebrand disease, respectively) which demonstrate the crucial role of vWF in atherothrombosis. Therapeutic inhibition of VWF by novel agents appears particularly promising for secondary prevention of stroke recurrence in specific sub-groups of patients such as those suffering from large artery atherosclerosis, as designated according to the TOAST classification.
Keywords: stroke prevention; von Willebrand factor; high shear rates; individualized treatment